1997
DOI: 10.1038/sj.bjp.0700915
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary characterization of the role of protein serine/ threonine phosphatases in the regulation of human lung mast cell function

Abstract: 1 Okadaic acid, a cell permeant inhibitor of protein serine/threonine phosphatases (PPs), attenuated the IgE-dependent release of mediators from human lung mast cells (HLMC). The concentration of okadaic acid required to inhibit by 50% (IC 50 ) the IgE-dependent release of histamine was 0.2 mM. Okadaic acid also inhibited the IgE-mediated generation of prostaglandin D 2 (PGD 2 ) and sulphopeptidoleukotrienes (sLT) with IC 50 values of 0.2 mM and 0.6 mM respectively. 2 The IgE-mediated generation of histamine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…This increased cytokine production was mediated by an increase in the phosphorylation of p38 MAPK following PP2A inhibition by okadaic acid [8]. In addition, the administration of okadaic acid to human lung mast cells resulted in the inhibition of IgE-dependent histamine release and prostaglandin D2 and sulphopeptidoleukotriene generation [85]. Thus, protein serine/threonine phosphatases, in particular PP2A, can both positively and negatively regulate mast cell functions.…”
Section: Regulation By Protein Serine/threonine Phosphatasesmentioning
confidence: 95%
“…This increased cytokine production was mediated by an increase in the phosphorylation of p38 MAPK following PP2A inhibition by okadaic acid [8]. In addition, the administration of okadaic acid to human lung mast cells resulted in the inhibition of IgE-dependent histamine release and prostaglandin D2 and sulphopeptidoleukotriene generation [85]. Thus, protein serine/threonine phosphatases, in particular PP2A, can both positively and negatively regulate mast cell functions.…”
Section: Regulation By Protein Serine/threonine Phosphatasesmentioning
confidence: 95%
“…5C). 29 Moreover, the catalytically inactive PPP1 mutant (H248K), 30 could not decrease the phosphorylation of ATG16L1. These data suggest that PPP1, but not PPP2CA, dephosphorylates CSNK2-phosphorylated ATG16L1 in vitro, which indicates that PPP1 may be the major phosphatase responsible for the dephosphorylation of ATG16L1.…”
Section: Ppp1 Dephosphorylated Atg16l1 In Vitromentioning
confidence: 99%
“…For inhibitor-2 (New England Biolabs, P0755) treatment, 2.5 units of inhibitor-2 were added. The reaction was incubated at 30 C for 30 min. The beads and supernatant fraction were carefully separated by centrifugation.…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to recycling, it appears that dephosphorylation of the receptor, by a PP2A-like phosphatase, is involved in ensuring receptor re-expression. Our previous studies (Peirce et al 1997) provided a framework for the study here to determine the role, if any, of PP2A in desensitization/re-sensitization of mast cells. Those studies (and later ones) had shown that mast cells expressed PP2A but that inhibition of PP2A with the highly selective inhibitor fostriecin had no effect on IgE-mediated histamine release (Bastan et al 2001).…”
Section: Discussionmentioning
confidence: 99%